PENGARUH ROM EXERCISE DINI TERHADAP INTENSITAS NYERI PADA PASIEN POST OPERASI FRAKTUR EKSTREMITAS ATAS DAN BAWAH DI RUMKITAL Dr. MIDIYATO SURATANI TANJUNGPINANG - Sembiring, Suryani Florentina Br; Widiastuti , Linda; Yanti , Masyitah Novia (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Extremity of fractures make it difficult for a person to mobilize and feel pain after surgery. This has an impact on hampering the patient's rehabilitation phase. Early ROM exercise is important for post-operative patients to restore muscle function, improve blood circulation, prevent contractures and muscle atrophy. The aim of the study was to determine the effect of early ROM exercise on pain intensity in post-extremity fracture surgery patients at Rumkital Dr. Midiyato Suratani Tanjungpinang. This research design : is quasi experimental (quasi-experiment) with a one group pre and post test design, sample size of 30 with total sampling technique. Data collection tool with observation sheet and hayward pain scale. Data analysis used the wilcoxon test. Research results : The intensity of pain on the first post-operative day before early ROM exercise was mostly in the give up category for 28 respondents (93.3%) with a median of 3.00. The intensity of pain on the first day after early ROM exercise was mostly in the mild pain category for 26 respondents (86.7%) with a median of 2,00. The pain intensity of the respondents on the second day before early ROM exercise was mostly in the pain category which was a give up for 17 respondents (56.7%) with a median of 3,00. The pain intensity of respondents on the second day after early ROM exercise was mostly in the mild pain category 28 respondents (93.3%) with a median of 2.00. The wilcoxon test results have a p value of 0.000 (≤0.05), meaning that there is an influence of early ROM exercise on pain intensity in post-extremity fracture surgery patients at Rumkital Dr. Midiyato Suratani Tanjungpinang. Discussion: Early implementation of ROM exercise can reduce pain intensity. This action can be used as a way to reduce pain intensity in post-extremity fracture surgery patients..